Role of N6-Methyladenosine Methylation Regulators in the Drug Therapy of Digestive System Tumours - Xia, Zhelin; Kong, Fanhua; Wang, Kunpeng; Zhang, Xin (Frontiers in Pharmacology, 2022)
Digestive system tumors, including stomach, colon, esophagus, liver, and pancreas tumors, are serious diseases affecting human health. Although surgical treatment and postoperative chemoradiotherapy effectively improve patient survival, current diagnostic and therapeutic strategies for digestive system tumors are not sensitive and specific. Moreover, the tolerance of tumor to drug therapy is enhanced due to the heterogeneity of tumor cells. Thus, primary or acquired treatment resistance has become the main challenge of current chemotherapy. N6-methyladenosine (m6A) plays a variety of biological functions in RNA modification. m6A modification, a key regulator of transcription expression, regulates RNA metabolism and biological processes through the interaction of m6A methyltransferase (“writers”) and demethylase (“erasers”) and the binding protein decoding m6A methylation (“readers”). Increasing studies showed that m6A modification regulates the occurrence and development of tumors and is a potential driving factor of tumor drug resistance. This review systematically summarizes the regulatory mechanisms of m6A modification in the drug therapy of digestive system malignancies in recent years and clarifies the related mechanisms and therapeutic prospects of m6A modification in the tolerance of digestive system malignancies to drug therapy.